1988
DOI: 10.1210/jcem-67-4-785
|View full text |Cite
|
Sign up to set email alerts
|

Defects inβ-Cell Function and Insulin Sensitivity in Normoglycemic Streptozocin-Treated Baboons: A Model of Preclinical Insulin-Dependent Diabetes*

Abstract: During the preclinical period of human insulin-dependent diabetes, both impaired pancreatic beta-cell function and increased insulin resistance are found, although normoglycemia is preserved. To better understand the changes in beta-cell function and insulin sensitivity that occur in preclinical insulin-dependent diabetes, we performed a panel of in vivo beta-cell function tests and measured insulin sensitivity in adolescent male baboons both in normal health and after a small dose of streptozocin which did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 29 publications
2
41
1
Order By: Relevance
“…In STZ-200 animals during NA, basal insulin was 168±48 pM before glu- 'cI 10 15 20 Glucose ( mM ) (25) and allows measurement of insulin secretion and insulin sensitivity on the same day. We have shown previously, both in normal humans (3) and baboons (2), that there is an inverse correlation between insulin secretion and insulin sensitivity such that changes in either one can only be fully appreciated when considered in relation to the other (3,4). The baboons in this study showed a profound reduction in insulin sensitivity after 2-3 wk of NA treatment comparable to that seen in human adults (21).…”
Section: B Cellfunction Testssupporting
confidence: 69%
See 2 more Smart Citations
“…In STZ-200 animals during NA, basal insulin was 168±48 pM before glu- 'cI 10 15 20 Glucose ( mM ) (25) and allows measurement of insulin secretion and insulin sensitivity on the same day. We have shown previously, both in normal humans (3) and baboons (2), that there is an inverse correlation between insulin secretion and insulin sensitivity such that changes in either one can only be fully appreciated when considered in relation to the other (3,4). The baboons in this study showed a profound reduction in insulin sensitivity after 2-3 wk of NA treatment comparable to that seen in human adults (21).…”
Section: B Cellfunction Testssupporting
confidence: 69%
“…4). (2,33). Nonenzymatic glycosylation of hemoglobin in mammals is determined by three major variables: mean plasma glucose concentration, red cell life span and red cell permeability (33).…”
Section: B Cellfunction Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether β cell dysfunction or reduced β cell mass precedes clinical onset of diabetes remains an open question. However, in mice, surgical and chemical reductions of β cell volume demonstrate that the functional adaptation of the normal β cell prevents a rise in fasting glucose or reduction in the first phase of insulin secretion (92,93), suggesting that β cell dysfunction, rather than a decrease in β cell mass, is likely to be more closely associated with the pathophysiology of T2DM.…”
Section: Clinical Implications Of Dynamics Of Insulin Secretionmentioning
confidence: 99%
“…We would suggest that they are compensating for their numerical loss and are near their maximal output per cell, so that the reduced number of ␤-cells are sufficient to prevent fasting hyperglycemia. Another animal model for ␤-cell loss is the streptozotocin-treated baboon, which demonstrates a similar pattern of functional change (8).…”
Section: ␤-Cell Massmentioning
confidence: 99%